The role of inflammation, oxidative stress, angiogenesis, and apoptosis in the pathophysiology of endometriosis: Basic science and new insights based on gene expression - Samimi, Mansooreh; Pourhanifeh, Mohammad Hossein; Mehdizadehkashi, Abolfazl; Eftekhar, Tahereh; Asemi, Zatollah (Journal of cellular physiology, 2019)
Endometriosis is a frequent and chronic illness in young women which could be defined by the existence of endometrial stroma and glands outside of the normal site of the lining of the uterus. It has painful symptoms. The advanced stage of endometriosis may lead to gynecological malignancies, such as ovarian cancer, and other complications, including infertility. However, its exact physiopathology is not well known. Recent studies have shown the possible roles of inflammation along with oxidative stress. Additionally, angiogenesis and apoptosis dysregulation contribute to endometriosis pathophysiology. Therapeutic strategies and continuing attempts, to conquer endometriosis should be done regarding molecular signaling pathways. Thus, the present review summarizes current studies and focuses on molecular mechanisms. Recent studies have shown the possible roles of inflammation along with oxidative stress. Additionally, angiogenesis and apoptosis dysregulation contribute to endometriosis pathophysiology. Therapeutic strategies and continuing attempts, to conquer endometriosis should be done regarding molecular signaling pathways. Thus, the present review summarizes current studies and focuses on molecular mechanisms.